1991
DOI: 10.1113/jphysiol.1991.sp018722
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic secretion of quanta from nerve terminals in avian ciliary ganglia modulated by adenosine.

Abstract: SUMMARY1. The effects of adenosine on the probability of secretion of acetylcholine quanta and on presynaptic and postsynaptic action potentials was examined in the posthatched avian ciliary ganglion.2. Adenosine (20 /tM) reduced the average size of the excitatory postsynaptic potential (EPSP) by 33 %. This was due to a decrease in quantal content of the EPSP (mn). The effect was blocked by theophylline (50 /IM). 4. Plateau-type action potentials with a large calcium component were generated in the ciliary neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Endogenous adenosine modulates transmission at preganglionic nerve terminals in avian ciliary ganglia, where it acts to depress the secretion of acetylcholine quanta (Bennett & Ho, 1991). This purine nucleoside also reduces the duration of plateau-type action potentials generated in both ciliary neurones and their preganglionic calyciform nerve terminals following exposure to tetraethylammonium ions (Bennett & Ho, 1991). These observations suggest that adenosine acts to reduce the inward calcium current associated with such plateau-type action potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous adenosine modulates transmission at preganglionic nerve terminals in avian ciliary ganglia, where it acts to depress the secretion of acetylcholine quanta (Bennett & Ho, 1991). This purine nucleoside also reduces the duration of plateau-type action potentials generated in both ciliary neurones and their preganglionic calyciform nerve terminals following exposure to tetraethylammonium ions (Bennett & Ho, 1991). These observations suggest that adenosine acts to reduce the inward calcium current associated with such plateau-type action potentials.…”
Section: Introductionmentioning
confidence: 99%
“…The avian ciliary ganglion provides an opportunity to elucidate the mechanism of action of adenosine as transmission is modulated by endogenous purine nucleotides at this synapse (Bennett & Ho, 1991). Furthermore the synapse possesses giant calyciform nerve terminals that are accessible to single electrode voltage clamp (Martin & Pilar, 1963).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Furthermore the synapse possesses giant calyciform nerve terminals that are accessible to single electrode voltage clamp (Martin & Pilar, 1963). Such studies have shown that adenosine hyperpolarizes nerve terminals, suggesting that its action increases the outward potassium currents (Bennett & Ho, 1991). Adenosine hyperpolarizes atrial cells by activating IM potassium channels via GTP-binding proteins (Kurachi et al, 1986).…”
Section: Introduction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the neurone soma there are delayed rectifier channels, calcium-activated potassium channels, inward rectifier potassium channels, cholinoceptor agonist activated channels, fast-transient potassium channels, and sodium-activated potassium channels . A number of different potassium channels have also been identified in the calyciform nerve terminal: these include delayed rectifier channels, inward rectifier channels and calcium-activated potassium channels (Bennett & Ho, 1991;Fletcher & Chiappinelli, 1992). The identity of the type of Ik(ca) is not clear, although an Ik(Ca) is blocked by tetraethylammonium ions (TEA; Bennett & Ho, 1992), and it is known that the fast Ik(ca), Ic, which contributes to the repolarization of the action potential is very sensitive to TEA in autonomic ganglia (Lancaster & Pennefather, 1987;Marsh & Brown, 1991).…”
Section: Discussionmentioning
confidence: 99%